Insight of Genus Corynebacterium: Ascertaining the Role of Pathogenic and Non-pathogenic Species - Oliveira, Alberto; Oliveira, Leticia C.; Aburjaile, Flavia; Benevides, Leandro; Tiwari, Sandeep; Jamal, Syed B.; Silva, Arthur; Figueiredo, Henrique C. P.; Ghosh, Preetam; Portela, Ricardo W.; De Carvalho Azevedo, Vasco A.; Wattam, Alice R. (Frontiers in Microbiology, 2017)
This review gathers recent information about genomic and transcriptomic studies in the Corynebacterium genus, exploring, for example, prediction of pathogenicity islands and stress response in different pathogenic and non-pathogenic species. In addition, is described several phylogeny studies to Corynebacterium, exploring since the identification of species until biological speciation in one species belonging to the genus Corynebacterium. Important concepts associated with virulence highlighting the role of Pld protein and Tox gene. The adhesion, characteristic of virulence factor, was described using the sortase mechanism that is associated to anchorage to the cell wall. In addition, survival inside the host cell and some diseases, were too addressed for pathogenic corynebacteria, while important biochemical pathways and biotechnological applications retain the focus of this review for non-pathogenic corynebacteria. Concluding, this review broadly explores characteristics in genus Corynebacterium showing to have strong relevance inside the medical, veterinary and biotechnology field.